Evidence of earthquake-induced liquefaction obtained from GeoEye-1 images. Issue 2 (26th April 2012) - Orense, R.; Wotherspoon, L.; Cubrinovski, M.; Bowman, E.; Pender, M.
Abstract : A most significant effect of the M w 7·1 Darfield earthquake of 4 September 2010 was widespread liquefaction and lateral spreading in the eastern parts of the city of Christchurch and the surrounding region. Large volumes of ejecta were deposited on the ground surface. A few hours after the earthquake, a GeoEye-1 image of part of the area affected by the earthquake was captured and subsequently appeared on Google Earth. Saturday 4 September was a clear day in Canterbury, so this image provided good evidence of liquefaction in the form of piles of ejected sand on the ground surface in Christchurch and the surrounding region. This letter illustrates the effectiveness of public domain GeoEye-1 images at indicating places where liquefaction has occurred. Not surprisingly, the colour contrast between the material ejected and the surface onto which the material was deposited was an important factor in identification. In addition, although a considerable volume of water was observed to have been ejected during the liquefaction, in some places, the images gave the impression that the extent of the liquefaction was much greater than was found to be the case during subsequent on-ground reconnaissance. These observations were confirmed following the M w 6·2 Christchurch earthquake (an aftershock of the Darfield event) on 22 February 2011. A most significant effect of the M w  7·1 Darfield earthquake of 4 September 2010 was widespread liquefaction and lateral spreading in the eastern parts of the city of Christchurch and the surrounding region. Large volumes of ejecta were deposited on the ground surface. A few hours after the earthquake, a GeoEye-1 image of part of the area affected by the earthquake was captured and subsequently appeared on Google Earth. Saturday 4 September was a clear day in Canterbury, so this image provided good evidence of liquefaction in the form of piles of ejected sand on the ground surface in Christchurch and the surrounding region. This letter illustrates the effectiveness of public domain GeoEye-1 images at indicating places where liquefaction has occurred. Not surprisingly, the colour contrast between the material ejected and the surface onto which the material was deposited was an important factor in identification. In addition, although a considerable volume of water was observed to have been ejected during the liquefaction, in some places, the images gave the impression that the extent of the liquefaction was much greater than was found to be the case during subsequent on-ground reconnaissance. These observations were confirmed following the M w  6·2 Christchurch earthquake (an aftershock of the Darfield event) on 22 February 2011.